Inovasi Materi Ajar Teks Berita Berbantuan Aplikasi Quillbot untuk Meningkatkan Kemampuan Menulis Teks Berita Siswa Kelas XI Inglanfis SMA Negeri 1 Percut Sei Tuan - Annarha Nayla; Ayla Zahra Adnan; Mesti Herniat Permata Zebua; Miyana Dewi E. Sitepu; Nazwa Gadisa; Trisnawati Hutagalung; Nurul Azizah (Khatulistiwa: Jurnal Pendidikan dan Sosial Humaniora, 2026)
This study aims to develop news-text teaching materials assisted by QuillBot as a learning medium for Indonesian Language instruction in Grade XI, focusing on improving students’ understanding of news-text structure and their writing skills. This research employed a Research and Development (R&D) approach using the ADDIE model, consisting of five stages: analysis, design, development, implementation, and evaluation. Data were collected through classroom observations, teacher interviews, questionnaires, and student comprehension tests. The findings indicate that most students had a sufficient understanding of news texts prior to the use of QuillBot; however, they still experienced difficulties in organizing their ideas systematically and avoiding writing errors. Through the use of QuillBot, students were able to paraphrase news texts, refine grammar, and improve linguistic accuracy and fluency. Expert validations revealed that the developed teaching material was deemed “feasible without revision” by the material expert and “suitable for use without revision” by the media expert. Effectiveness testing also showed improvement in student learning outcomes, reflected in increased average scores, higher mastery levels, and positive student responses toward the integration of QuillBot in the learning process. This study concludes that QuillBot provides an engaging and interactive learning experience, enhances student motivation in studying news texts, and supports the integration of AI-based technology in the classroom. Therefore, QuillBot can serve as an effective and innovative AI-assisted learning medium that strengthens students’ digital literacy skills.